The impact of stress on employees' performance and satisfaction at Jabatan Ketua Menteri Melaka / Nur'aini Buang - Buang, Nur'aini (Faculty of Business and Management, 2007)
Stress is feelings that make individuals feel bad in his or her life in a moment. Sometimes stress can make people angry, moody and cannot do their work appropriately. Even though stress is bad, yet, there are stresses that give good ones to individual life. The main objective of this paper is to identify the impact of job stress on employees' performance and job satisfaction at Jabatan Ketua Menteri Melaka. It also will help the company to determine whether their new strategies had been done effectively or otherwise. Thus, the objectives of the study are to determine factors that contribute to stress among employees, to examine the impact of job stress on employees' performance and to examine the impact of job stress on employees' satisfaction. The scope of the study focuses on organizational stress factors and its impact on employees' performance and job satisfaction . The respondents are the employees who work in Jabatan Ketua Menteri Melaka. In this study, researcher used secondary and primary data in collecting the necessary data. The sampling type used was the stratified sampling where 4 departments from Jabatan Ketua Menteri Melaka and simple random sampling where 40 respondents are being chosen to answer the questionnaires. In order to run data, Statistical Package for Social Science (SPSS) are been used. A factor analysis was done for the purpose of determining the construct validity of the questionnaire and three (3) variables were grouped in the organizational stress factors. The findings give a better understanding about level of employee stress in government sectors.